DEMAND ANALYSIS FOR STRATEGIC FOOD IN INDONESIA DURING ECONOMIC CRISIS AND ITS IMPLICATION ON FOOD CONSUMPTION AMONG HOUSEHOLDS WITH CHILDREN UNDER TWO YEARS - Resti Mauludyani, Anna Vipta; Fahmida, Umi; Santika, Otte (PERSATUAN AHLI GIZI INDONESIA, 2013)
The objective of the study is to analyze demand elasticity for strategic foods during economic crisis and its implication on food and nutrient consumption among household in Indonesia. This ecological study was conducted to 14,767 households owned children less than two years included in National Socioeconomic Survey 2007. Analysis was conducted by using econometric model of Double-Log Regression in SAS program. Result of analysis showed that the own-price elasticities were all found to be negative as expected, meaning that increased price of strategic food tended to reduce its demand. Inconclusion, the effect of food crisis was visible to most of the strategic foods which their demand tendedto be highly affected by price changes. This effect was mostly seen in rural and low income household swhich had limited income to purchase food. Improved income tended to increase demand of strategic foods. Demand on protein sources were highly affected by income changes.Keywords: demand analysis, strategic food, food consumption, nutrient intake.